A Model of Academic Well-Being: An Integrative Review of Faculty and Staff Mental Health in Higher Education - Arbin Janu Setiyowati; Ahmad Munjin Nasih; Poppy Puspitasari; Hetti Rahmawati; Awalya Siska Pratiwi; Hengki Tri Hidayatullah (Universitas PGRI Yogyakarta, 2026)
The well-being of faculty and staff in higher education has increasingly become a global concern, particularly during the COVID-19 pandemic. However, existing research remains fragmented and lacks a unified theoretical framework. This study aimed to synthesize empirical evidence on faculty and staff mental health and to develop an integrative Academic Well-Being model for higher-education settings. A Systematic Integrative Review (SLR) was conducted in accordance with PRISMA 2020. Seventeen peer-reviewed international studies published between 2017 and 2025 were analyzed through thematic synthesis. The findings reveal that academic well-being is a multidimensional construct encompassing eight key dimensions: psychological, social, organizational, spiritual, physical, digital, financial, and cultural policy. Psychological well-being and empathetic leadership emerged as central determinants, while digital adaptation, spiritual meaning, and financial security are emerging factors in the post-pandemic period. The synthesis resulted in an Ecological Model of Academic Well-Being (EAWB) comprising four nested levels: individual, interpersonal, organizational, and cultural systemic that interact dynamically to shape mental health and professional flourishing in academia. The model highlights that sustainable well-being arises not from personal resilience but from compassionate leadership, organizational justice, and inclusive cultures. This review contributes a holistic framework for transforming universities into compassionate ecosystems. Keywords: academic well-being model, mental health, university staff, higher education